Identification of Novel Genetic Loci for Intraocular Pressure: A Genomewide Scan of the Beaver Dam Eye Study - Duggal, Priya (2007)
CLINICAL RELEVANCE: Glaucoma is a leading cause of blindness in the world, and the identification of genes that contribute to this disease is essential. Elevated intraocular pressure (IOP) is a principal risk factor for primary open-angle glaucoma (POAG), and an intriguing quantitative trait that may strongly influence the development of disease. OBJECTIVES: The objective of this study was to identify genetic loci that control IOP. METHODS: We performed a genomewide scan of IOP, using 486 pedigrees ascertained through a population based cohort, the Beaver Dam Eye Study. Linkage analysis was performed using the modified Haseman-Elston regression models and variance components linkage analysis. RESULTS: Seven regions of interest were identified on chromosomes 2, 5, 6, 7, 12, 15 and 19. The novel linkage region on chromosome 19p had an empirical multipoint pvalue of 6.1×10(−5). Two of the regions (2 and 19) are especially interesting since each has been identified as potential linkage regions for blood pressure. CONCLUSIONS: The results of this genomewide scan provide evidence that a quantitative trait locus (QTL) may influence elevated IOP and may co-localize with blood pressure loci. These loci may control systemic pressure reflected in the eye and vascular system.